A bimodal high-strength electric porcelain and its preparation method
By using bimodal particle distribution, nanobubble enhancement and laser self-propagation sintering technologies in electroceramic materials, the shortcomings of traditional electroceramic materials in mechanical strength, insulation performance and production efficiency are solved, and higher performance indicators and lower production costs are achieved.
Patent Information
- Application Number
- CN202411750676.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional high-strength electroceramic materials have shortcomings in mechanical strength, insulation performance, sintering temperature and production efficiency, and cannot meet the higher requirements of high-voltage transmission systems.
By optimizing the particle ratio and structure, the sintering temperature and time are reduced, and the density and insulation performance of the material are improved.
It significantly improves the mechanical strength, insulation performance and toughness of the material, reduces sintering temperature and production energy consumption, enhances corrosion resistance and long-term stability, and improves production efficiency and economy.
Smart Images

Figure CN119735432A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material science and electric power equipment, and specifically relates to a bimodal high-strength electric porcelain and a preparation method thereof. Background Art
[0002] With the rapid development of the power system, high-voltage transmission lines and distribution networks have increasingly higher requirements for the performance of insulators. As an important part of transmission lines, the performance of insulators directly affects the stability and safety of power equipment. Traditional high-strength insulators usually use a single particle size distribution and conventional sintering process, which has the following shortcomings:
[0003] Limited mechanical strength:
[0004] The uneven distribution of particles in traditional electrical porcelain leads to insufficient density, a large number of pores between particles, and a bending strength of usually 350-380MPa, which cannot meet the higher mechanical strength requirements of high-voltage transmission systems.
[0005] Lower insulation performance:
[0006] The presence of local conductive paths or defects in the material leads to increased leakage current, and the insulation performance is usually 15-18kV / mm, which is difficult to meet the insulation capacity requirements in high-voltage power transmission environments.
[0007] High sintering temperature and high energy consumption:
[0008] Traditional sintering processes usually require high temperatures of 1400-1500°C, which not only consumes a lot of energy, but also easily leads to uneven thermal expansion of materials, increasing production costs.
[0009] Insufficient corrosion resistance:
[0010] Insulators are exposed to complex environmental conditions for a long time (such as acid rain, salt spray, high humidity, etc.). Traditional materials have insufficient chemical stability and are susceptible to surface corrosion, which shortens the life of the insulators.
[0011] Low production efficiency:
[0012] The production process of traditional electrical porcelain includes multiple sintering and long-term heat treatment, which leads to a long production cycle, affecting the economy and market competitiveness of large-scale production.
[0013] In recent years, in order to improve the performance of insulators, researchers have tried to improve insulators by optimizing particle distribution, introducing nanomaterials, adjusting sintering processes, etc. However, the existing technologies mostly use a single particle size distribution, which fails to fully utilize the synergistic advantages of bimodal particle distribution; at the same time, the existing sintering technology mainly relies on traditional heating methods, lacks precise control of the sintering process, and cannot effectively reduce the sintering temperature and time. Summary of the invention
[0014] The purpose of the present invention is to provide a bimodal high-strength electrical porcelain and a preparation method thereof. The present invention achieves multiple breakthroughs in material properties and production efficiency through the synergistic effect of technologies such as bimodal particle distribution, nanobubble enhancement, laser self-propagating sintering and surface functionalization. Compared with the prior art, the present invention has the advantages of higher mechanical strength, insulation performance and toughness, lower sintering temperature and production energy consumption, more excellent corrosion resistance and long-term stability, and higher production efficiency and economy.
[0015] The technical solution adopted by the present invention is as follows:
[0016] A bimodal high-strength insulator, the insulator is composed of the following raw materials by mass percentage:
[0017] Alumina (Al2O3): 40-55%,
[0018] Fly ash: 15-25%,
[0019] Silicon dioxide (SiO2): 8-12%,
[0020] Feldspar (K2O·Al2O3·SiO2): 5-10%,
[0021] Nano silicon carbide (SiC): 3-5%,
[0022] Zirconium oxide (ZrO2): 2-4%,
[0023] Borate (B2O3): 1-2%,
[0024] Silicon nitride (Si3N4): 0.5-1%,
[0025] The electric porcelain presents a bimodal particle distribution, with a large particle size of 10-20 μm and a small particle size of 0.5-1 μm, wherein the large particles account for 50-60% of the total formula and the small particles account for 40-50% of the total formula.
[0026] The small particles in the raw material are coated with zirconium oxide and silicon nitride by atomic layer deposition, and the coating thickness is 5-10nm.
[0027] The formula further comprises a nano bubble enhancement component, wherein the nano bubbles are composed of nitrogen or oxygen, have a diameter of 0.5-1 μm, and a volume fraction of 0.2-0.5%.
[0028] A method for preparing a bimodal high-strength electrical porcelain comprises the following steps:
[0029] S1. Bimodal particle preparation and mixing:
[0030] Large particles and small particles are distributed in a mass ratio of 55:45;
[0031] Small particles are coated with zirconium oxide and silicon nitride by atomic layer deposition;
[0032] Mix large particles, small particles, fly ash, silica, feldspar, and borate, add dispersant and stir evenly;
[0033] S2. Nanobubble enhanced granulation:
[0034] The mixed slurry is injected into a nanobubble generator to form nanobubbles with a diameter of 0.5-1 μm;
[0035] The slurry is prepared into powder particles containing bubbles using spray drying, with a particle size of 50-200 μm;
[0036] S3. Isostatic pressing:
[0037] The powder is pressed in a mold at a pressure of 100-200 MPa, while a programmable electric field of 500-1000 V / cm is applied to induce directional alignment of the particles;
[0038] S4. Laser self-propagating sintering:
[0039] The sintering reaction is triggered by a pulsed laser, with a sintering temperature of 1200-1300°C and a sintering time of 15-30 minutes;
[0040] During the sintering process, nano-silicon carbide and silicon nitride self-generate functional ceramic films to enhance material strength and insulation performance;
[0041] S5. Post-treatment and surface functionalization:
[0042] After secondary sintering at 800-1000℃, the density and wear resistance are further improved.
[0043] The solid-liquid ratio in the mixed slurry is 50:50, the dispersant is polyethylene glycol, and the addition amount is 0.5-1%.
[0044] The laser power in the laser self-propagating sintering is 100-500W, and the self-propagating reaction is triggered by 2% metal nitride contained in the powder.
[0045] Wherein, the holding time of the isostatic pressing is 2-3 minutes.
[0046] The nanobubbles are stabilized by a surfactant, and the bubble injection pressure is 0.1-0.3 MPa.
[0047] The thickness of the functional ceramic film generated during the post-treatment is 0.5-1 μm, which is used to improve the corrosion resistance of the electrical ceramic.
[0048] Wherein, during the electric field induced alignment process, the applied electric field frequency is 50-100 Hz, which is used to enhance the directionality and density of the particles.
[0049] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0050] 1. Higher mechanical strength
[0051] Bimodal particle distribution: The present invention improves the close bonding between particles by optimizing the ratio of large particles to small particles (55:45) and functionalization, which significantly improves the flexural strength. Compared with the prior art, the flexural strength of the present invention can reach 460MPa, while the traditional electric porcelain is usually 350-380MPa.
[0052] Isostatic pressing and electric field induced alignment: The electric field is introduced during the isostatic pressing stage to induce particle alignment, further optimizing the microstructure, reducing pores and cracks, and significantly improving the overall mechanical properties.
[0053] 2. Excellent insulation performance
[0054] Generation of surface functional film: The laser sintering stage is combined with low-temperature post-sintering to generate a uniform and dense ceramic glass film. The high resistivity and good coverage of the film effectively eliminate the high electric field concentration effect, making the insulation performance reach 25kV / mm, which is about 30-40% higher than the existing technology.
[0055] Nanobubble enhancement: The introduction of nanobubbles forms a uniformly distributed microporous structure during the sintering process, which reduces the local conductive path and further improves the insulation performance.
[0056] 3. Lower sintering temperature and energy consumption
[0057] Laser self-propagating sintering technology: using borates and feldspar as sintering aids, triggering a self-propagating reaction under the action of local high temperature of the laser, greatly reducing the overall sintering temperature to 1200-1300°C. Compared with the traditional sintering technology that requires 1400-1500°C, this invention reduces energy consumption by about 20-30%.
[0058] Fast sintering: Laser sintering combined with self-propagating reaction shortens the sintering time to 15-30 minutes, while traditional sintering usually takes several hours, significantly improving production efficiency.
[0059] 4. Stronger corrosion resistance
[0060] Protective effect of ceramic glass film: The surface ceramic glass film is cured during high-temperature sintering and post-processing stages. It has extremely high chemical inertness and can effectively resist acid, alkali and moisture erosion. Its corrosion resistance is more than 50% higher than that of traditional materials.
[0061] Functional reinforcement materials: The synergistic effect of nano silicon carbide (SiC) and silicon nitride (Si3N4) enhances the surface hardness and crack propagation resistance of the material, thereby extending the service life of the electrical porcelain.
[0062] 5. Higher toughness and reliability
[0063] Microporous structure regulation: The introduction of nanobubbles forms a uniform microporous structure after sintering, which not only improves the thermal expansion buffering capacity of the material, but also reduces the crack concentration points, and the toughness is significantly improved to 6.6MPa·m 1 / 2 , higher than the 4.5-5MPa·m of traditional technology 1 / 2 .
[0064] Low-temperature post-sintering optimization: Post-sintering releases the residual stress generated during the laser sintering process, further improving the reliability and durability of the material.
[0065] 6. Reduced overall production costs
[0066] Sintering aid and self-propagating reaction: The liquid phase diffusion effect of the sintering aid combined with the self-propagating reaction significantly reduces the sintering temperature and energy consumption.
[0067] Rapid prototyping and high efficiency: the combination of isostatic pressing, electric field induced alignment and laser rapid sintering technology shortens the production cycle by about 40% and significantly reduces the cost per piece. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 It is a schematic diagram of the preparation method of the bimodal high-strength electrical porcelain of the present invention. DETAILED DESCRIPTION
[0069] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0070] The present invention relates to a bimodal high-strength insulator, which is composed of the following raw materials by mass percentage:
[0071]
[0072] See also Figure 1 The preparation method of the bimodal high-strength electrical porcelain of the present invention is as follows:
[0073] Step 1: Bimodal particle preparation and mixing
[0074] ① Bimodal particle distribution: Large particles: Select 10-20μm alumina particles (accounting for 50-60% of the formula).
[0075] Small particles: Grind materials such as fly ash and silica to 0.5-1μm.
[0076] Key parameters:
[0077] Mass ratio of large particles to small particles: 55:45.
[0078] Function of large particles: build the skeleton and provide mechanical support.
[0079] Function of small particles: fill gaps and enhance density.
[0080] Bimodal particle size distribution achieves densification and structural optimization during sintering by optimizing the ratio of large and small particles. Its core mechanisms include:
[0081] Large particles act as a skeleton: Large particles (10-20 μm) build a skeleton in the mixture, providing the main mechanical support and sintering stability. During the sintering process, large particles can effectively prevent the overall shrinkage of the material from being too large, thereby maintaining structural integrity and high strength.
[0082] Small particle filling and interface optimization: Small particles (0.5-1μm) fill the gaps between large particles, reduce porosity, and significantly improve the density of the material. The high specific surface area of small particles can accelerate grain boundary migration during sintering and promote the bonding strength between particles.
[0083] ② Functionalization of particle surface: Use atomic layer deposition (ALD) to coat small particles with zirconium oxide (ZrO2) and silicon nitride (Si3N4) to enhance interface reactivity.
[0084] Parameter range:
[0085] ALD coating thickness: 5-10nm. Too thin coating (<5nm): insufficient coverage of the particle surface, unable to significantly enhance the interfacial bonding. Too thick coating (>10nm): interface diffusion is hindered, which in turn reduces the bonding strength between particles.
[0086] Processing temperature: 250-300℃. Temperature below 250℃: insufficient coating reaction rate and poor coating uniformity. Temperature above 300℃: will cause coating decomposition or particle agglomeration, reducing the effectiveness of the coating.
[0087] ALD is a technique for precisely controlling coating thickness and uniformity to improve particle surface reactivity and sintering properties:
[0088] Enhanced interface reactivity: The zirconium oxide (ZrO2) coating on the surface of the small particles has high chemical and thermal stability, which can provide better interface bonding performance during the sintering process. The silicon nitride (Si3N4) coating has excellent crack resistance, which can improve the compressive strength of the small particles and reduce the generation of interface cracks.
[0089] Grain boundary migration promotion: The nanometer thickness of the ALD coating (5-10nm) can provide a uniform diffusion channel, accelerate grain boundary migration, and enhance the bonding strength between particles. The high surface energy of the coating can also reduce the sintering temperature and improve the density of the sintering.
[0090] ③ Particle mixing: Mix the two particles in proportion, add feldspar and borate as additives. Use a high shear mixer to mix evenly (speed 300-500rpm, time 15-30 minutes). Speed below 300rpm: Insufficient mixing, uneven particle distribution. Speed above 500rpm or too long: It is easy to cause particle breakage or weakened separation effect.
[0091] Mixing is the key to achieving uniform particle distribution and stable material properties. Its main mechanisms include:
[0092] Homogenization of particle size distribution: The high shear mixer mixes large and small particles thoroughly through rapid rotation (300-500rpm) to avoid particle agglomeration. The particles are dispersed through shear force and centrifugal force, so that additives (such as feldspar and borate) are evenly covered on the particle surface, optimizing sintering behavior.
[0093] Particle surface activation: Feldspar, as a sintering aid, can form a liquid phase in the early stage of sintering, promoting the flow and bonding between particles. Borates further enhance the filling effect of small particles by reducing surface tension.
[0094] Synergistic effect of optimized ratio: When large particles and small particles are mixed in a ratio of 55:45, the skeleton support function of large particles and the filling function of small particles can be maximized. This ratio ensures the densification of the material while avoiding the sintering instability caused by too high a ratio of small particles.
[0095] Step 2: Nanobubble Enhanced Granulation
[0096] ① Slurry preparation: Add the mixed particles into deionized water to prepare slurry at a solid-liquid ratio of (50:50). Add a dispersant (such as polyethylene glycol, 0.5-1%).
[0097] Slurry preparation is a key step to ensure uniform particle dispersion, stable bubble generation and subsequent spray granulation effect. Its main mechanism is as follows:
[0098] The role of solid-liquid ratio (50:50): Controlling the solid-liquid ratio at 50:50 can ensure that the particles have good fluidity and dispersibility, and avoid the slurry being too thick to cause particle agglomeration, or too thin to cause unstable bubbles.
[0099] Function of dispersant: Adding dispersant (such as polyethylene glycol, 0.5-1%) can form an adsorption film on the surface of particles, reducing the surface tension between particles. Dispersant can effectively prevent particle sedimentation or agglomeration, improve the uniformity of slurry, and provide a good foundation for the stable generation of bubbles.
[0100] ②Nanobubble injection: Use a bubble generator to inject nitrogen (N2) or oxygen (O2) into the slurry to form nanobubbles with a diameter of 0.5-1μm. Nanobubble enhancement is achieved by introducing stable micron-sized bubbles into the slurry, which plays a role in structural regulation and performance optimization in the subsequent sintering stage. Its main mechanisms include:
[0101] Bubble generation and stabilization: Bubbles are injected into the slurry through a bubble generator. The pressure (0.1-0.3MPa) controls the bubble generation rate, ensuring that the bubble diameter is within the range of 0.5-1μm. The volume fraction of bubbles is controlled at 0.2-0.5 to ensure the formation of evenly distributed small pores between particles, providing a diffusion path during sintering. The bubble surface is stabilized by the dispersant to prevent the bubbles from breaking or merging.
[0102] Physical effects of nanobubbles: Bubbles are dispersed in the gaps between particles through volume to form a uniform microstructure. During the sintering process, the bubbles gradually collapse or dissolve, producing micropores or local expansion effects, which help to relieve inter-particle stress and optimize sintering densification.
[0103] Chemical effect of nanobubbles: Oxygen (O2) or nitrogen (N2) released during the dissolution of bubbles can adjust the sintering atmosphere and reduce excessive oxidation or sintering cracks.
[0104] Key parameters:
[0105] Bubble concentration: 0.2-0.5 volume fraction. Too low concentration (<0.2): Insufficient distribution of bubbles, unable to form an effective microporous structure. Too high concentration (>0.5): Excessive aggregation of bubbles, which may cause holes or cracks during sintering.
[0106] Injection pressure: 0.1-0.3MPa. Too low pressure (<0.1MPa): The bubble generation rate is insufficient and the bubble size is difficult to control. Too high pressure (>0.3MPa): It is easy to cause the bubbles to be too large or unstable, destroying the uniformity of the slurry.
[0107] ③ Spray granulation: spray-dry the slurry into powder particles. Drying temperature: 150-200℃. Too low temperature (<150℃): insufficient drying rate, easy agglomeration of particles. Too high temperature (>200℃): easy to cause surface cracks or internal stress of particles. Particle size control: 50-200μm (particles containing nanobubbles). Spray granulation is to convert the slurry into powder particles with good fluidity through spray drying technology, providing conditions for subsequent molding and sintering. Its main mechanism is as follows:
[0108] Particle size control: During the spray drying process, the slurry is atomized into droplets (the diameter is related to the nozzle size and the spray pressure). The drying temperature (150-200℃) ensures that the water evaporates quickly to form particles with a diameter of 50-200μm.
[0109] Retention of nanobubbles: During the drying process, the bubbles in the slurry are solidified in the particles, forming nanopores or locally expanded microstructures. The presence of nanobubbles helps to form a uniform microporous structure in the subsequent sintering stage, improving the toughness and thermal stability of the material.
[0110] Particle surface coating: additives such as feldspar and borate will be evenly distributed on the particle surface during the drying process, providing a liquid phase diffusion channel for subsequent sintering.
[0111] Step 3: Forming
[0112] ① Isostatic pressing: Use isostatic pressing equipment to press the powder into a mold. At the same time, a programmable electric field is applied to orient the particles in the direction of the electric field.
[0113] Isostatic pressing is a molding technology that uses high pressure to act on powder particles. Its core is to use uniform pressure and an external electric field to make the particles uniformly densified and oriented. The main mechanisms include:
[0114] Uniform pressure effect: In the isostatic pressing equipment, the powder particles are subjected to isotropic hydrostatic pressure (100-200MPa), which eliminates the pores in the particle accumulation and increases the density of the compact. Uniform pressure ensures that the particles are subjected to the same force in all directions, avoiding the problem of local cracks or inconsistent strength caused by uneven force on particles in traditional uniaxial pressing.
[0115] Skeleton support and densification: Large particles exist as a stable skeleton to resist particle deformation or breakage caused by excessive pressure. Small particles gradually fill the pores between the skeletons under pressure to achieve densification.
[0116] The external electric field induces polarization reaction of particles, causing them to align along the direction of the electric field and optimize the microstructure. The specific mechanism is as follows:
[0117] Particle polarization: The various phase components in the material (such as alumina, silica, feldspar, etc.) have different dielectric constants. When an electric field is applied, these particles will be polarized and an electric dipole moment will form on the surface. The electric dipole moment will generate Coulomb force under the action of the electric field force, driving the particles to align along the direction of the electric field.
[0118] Selective response of particles: Nano-silicon carbide and zirconium oxide respond more significantly to electric fields due to their high dielectric properties, and show stronger polarization ability in electric fields. Low dielectric particles (such as silicon dioxide) respond less to electric fields, but will achieve secondary directional arrangement driven by high dielectric particles.
[0119] Amplification effect of bimodal particle distribution on oriented alignment
[0120] Shielding effect of large particles: Large particles (10-20μm) are almost unaffected by the electric field due to their large mass and strong inertia, and mainly exist as a stable skeleton. These skeleton particles provide overall mechanical support and limit the excessive movement of small particles.
[0121] Directed arrangement of small particles: Small particles (0.5-1μm) are more likely to respond to the electric field force and align along the field direction under the action of the electric field. The arrangement of small particles fills the gaps between large particles and further optimizes the density and microstructural uniformity of the material.
[0122] Enhancement of alignment effect by surface functionalization
[0123] The role of ALD coating: ALD-coated zirconium oxide (ZrO2) and silicon nitride (Si3N4) form a highly active interface on the particle surface, which improves the polarization ability of the particles. The weak magnetism and high dielectric properties of the coating material further enhance the small particles' ability to respond to electric fields.
[0124] Influence of residual charge: During the mixing stage, the active sites and residual charges on the particle surface increase the electric field sensitivity of the particles, making it easier for small particles to align under the field effect.
[0125] Parameter range:
[0126] Pressure: 100-200MPa. Too low pressure (<100MPa): insufficient contact between particles, resulting in high porosity of the molded body. Too high pressure (>200MPa): may cause particle crushing or excessive interface compaction, affecting subsequent sintering.
[0127] Holding time: 2-3 minutes. Too short time (<2 minutes): The particles are not fully densified and the structure is loose. Too long time (>3 minutes): It may cause plastic deformation or failure of the particles.
[0128] Electric field strength: 500-1000V / cm. Too low strength (<500V / cm): insufficient electric field driving force, poor particle arrangement. Too high strength (>1000V / cm): may cause particle discharge or local breakdown, affecting molding quality.
[0129] Step 4: Laser self-propagating sintering
[0130] Sintering equipment: pulse laser sintering furnace is used. The laser triggers the sintering reaction, using the borate and feldspar in the powder as sintering aids to activate the low-temperature self-propagating reaction.
[0131] Self-propagating reaction: Nano-silicon carbide (SiC) and silicon nitride (Si3N4) in the powder form a functional ceramic film on the surface, enhancing wear resistance and insulation properties.
[0132] Self-propagating reaction is a series of exothermic chemical reactions occurring between particle interfaces during laser sintering. The specific mechanism is as follows:
[0133] Function of sintering aid: Borate (B2O3) and feldspar (K2O·Al2O3·SiO2) melt under laser heating to form a low-viscosity liquid phase to fill the pores between particles. The presence of the liquid phase reduces the diffusion barrier between particles and promotes grain boundary migration and bonding between particles.
[0134] Reaction of nano-silicon carbide (SiC) and silicon nitride (Si3N4): Under laser heating conditions, SiC and Si3N4 react on the surface to form a functional ceramic film. The functional film has high strength and excellent thermal stability, which can improve the wear resistance and insulation properties of the material.
[0135] Transfer of exothermic reaction: The exothermic heat generated by the self-propagating reaction is transferred between particles, further activating the surrounding unreacted areas, making the overall sintering process self-sustaining.
[0136] Sintering parameters:
[0137] Laser power: 100-500W. Too low power (<100W): The self-propagating reaction cannot be triggered, and the particles are difficult to sinter effectively. Too high power (>500W): It may cause overburning or thermal cracking of the particle surface.
[0138] Sintering temperature: 1200-1300℃. Too low temperature (<1200℃): the sintering aid cannot melt and the self-propagating reaction cannot continue. Too high temperature (>1300℃): it is easy to cause particle expansion or oxide film damage.
[0139] Sintering time: 15-30 minutes. Too short time (<15 minutes): incomplete sintering and insufficient density. Too long time (>30 minutes): prone to over-sintering or expansion of pores inside particles.
[0140] Step 5: Post-treatment and surface functionalization
[0141] ① Low-temperature post-sintering: Secondary sintering is carried out at 800-1000℃ to further improve the density.
[0142] Low temperature post-sintering (800-1000℃) is a further treatment of the primary sintered body after laser sintering to improve the density and stability of the material. Its main mechanism is as follows:
[0143] A small amount of pores may remain during the laser sintering stage, and low-temperature post-sintering further fills and closes the pores through solid-phase diffusion. At lower temperatures, grain boundary migration is still ongoing, but the sintering rate is slower, which helps avoid structural damage caused by over-sintering.
[0144] The temperature in the post-sintering stage is relatively low, which can effectively prevent excessive grain growth and further homogenize the grain distribution. The recrystallization effect makes the grains more closely bonded, improving the mechanical strength and crack resistance of the material.
[0145] The laser sintering stage may introduce thermal stress inside the material, which can be released by low-temperature post-sintering to avoid crack propagation or interface weakening. The structure formed by post-sintering is more stable and can adapt to the mechanical load or thermal cycle of the subsequent use environment.
[0146] ② Generation of surface functional film: Utilize the reaction in the laser sintering stage to make a layer of ceramic glass phase film form on the surface to improve the corrosion resistance and insulation performance.
[0147] The surface functional film is a ceramic glass phase film formed by a specific chemical reaction during the high temperature stage of laser sintering. It is further homogenized and enhanced in the post-processing stage. The specific mechanism is as follows:
[0148] During the laser sintering stage, sintering aids such as borates (B2O3) and feldspar (K2O·Al2O3·SiO2) melt at high temperatures and react with surface particles to generate a glassy phase. The glassy phase forms a uniform and dense film on the surface, which has good interface bonding with the base material.
[0149] In the post-sintering stage, the fluidity of the glass phase film decreases, and the structure gradually solidifies and homogenizes. The glass phase may contain trace amounts of zirconium oxide (ZrO2) and silicon dioxide (SiO2), and these nanoparticles enhance the hardness and wear resistance of the film.
[0150] Parameter range and performance indicators:
[0151] Process steps Parameter range ALD coating thickness 5-10nm Nano bubble particle size 0.5-1μm Sintering temperature 1200-1300℃ Sintering time 15-30 minutes Suppression pressure 100-200MPa
[0152] Performance indicators:
[0153] performance Target value Bending strength ≥400MPa Electrical insulation performance ≥20kV / mm density <![CDATA[3.5-3.8g / cm 3 ]]> toughness <![CDATA[≥6MPa·m 1 / 2 ]]>
[0154] The above formula and process have achieved innovation in the whole process from raw material selection to sintering process by introducing bimodal particle distribution, nanobubble enhancement and laser self-propagating sintering, significantly improving mechanical strength and insulation performance while reducing production costs. This technology is the first of its kind in the field of traditional electrical porcelain and has extremely high patent value and application potential.
[0155] Summary of six comparative tests of bimodal high-strength insulators and mainstream product formulas and test data:
[0156] Test formula table:
[0157]
[0158] Test parameter results table:
[0159]
[0160]
[0161] Test performance comparison:
[0162] Test 6 (optimal solution) had the highest performance among all tests, with a bending strength of 460MPa and an insulation performance of 25kV / mm, which was significantly better than other tests and control products.
[0163] Other tests have shown high performance through the optimization of different parameters (such as adjustment of fly ash and alumina ratio, optimization of sintering temperature, etc.), and all meet the target performance indicators.
[0164] Comparison product disadvantages:
[0165] The performance of the control products A and B is obviously worse, because they did not adopt innovative technologies such as bimodal particle distribution and laser self-propagating sintering, resulting in strength, insulation performance and toughness far lower than those of the present invention.
[0166] Optimization key points:
[0167] Bimodal particle distribution plays a decisive role in improving material density and strength.
[0168] The laser self-propagating sintering process optimizes the sintering process, reduces temperature and energy consumption, and significantly improves material properties.
[0169] in conclusion
[0170] The present invention is based on bimodal particle distribution and advanced technology, and comprehensively improves the performance indexes of the electrical porcelain.
[0171] Compared with existing mainstream products, the present invention has significant advantages in bending strength, insulation performance and toughness, and has extremely high technical application prospects.
[0172] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A bimodal high-strength insulator, characterized in that: The insulator is composed of the following raw materials by mass percentage: Alumina (Al2O3): 40-55%, Fly ash: 15-25%, Silicon dioxide (SiO2): 8-12%, Feldspar (K2O·Al2O3·SiO2): 5-10%, Nano silicon carbide (SiC): 3-5%, Zirconium oxide (ZrO2): 2-4%, Borate (B2O3): 1-2%, Silicon nitride (Si3N4): 0.5-1%, The electric porcelain presents a bimodal particle distribution, with a large particle size of 10-20 μm and a small particle size of 0.5-1 μm, wherein the large particles account for 50-60% of the total formula and the small particles account for 40-50% of the total formula.
2. A double-peak high-strength insulator according to claim 1, characterized in that: The small particles in the raw material are coated with zirconium oxide and silicon nitride by atomic layer deposition, and the coating thickness is 5-10nm.
3. A double-peak high-strength insulator according to claim 2, characterized in that: The formula further comprises a nano bubble enhancement component, wherein the nano bubbles are composed of nitrogen or oxygen, have a diameter of 0.5-1 μm, and a volume fraction of 0.2-0.5%.
4. A method for preparing a bimodal high-strength electrical porcelain, characterized in that: The following steps are involved: S1. Bimodal particle preparation and mixing: Large particles and small particles are distributed in a mass ratio of 55:45; Small particles are coated with zirconium oxide and silicon nitride by atomic layer deposition; Mix large particles, small particles, fly ash, silica, feldspar, and borate, add dispersant and stir evenly; S2. Nanobubble enhanced granulation: The mixed slurry is injected into a nanobubble generator to form nanobubbles with a diameter of 0.5-1 μm; The slurry is prepared into powder particles containing bubbles by spray drying, with a particle size of 50-200 μm; S3. Isostatic pressing: The powder is pressed in a mold at a pressure of 100-200 MPa, while a programmable electric field of 500-1000 V / cm is applied to induce directional alignment of the particles; S4. Laser self-propagating sintering: The sintering reaction is triggered by a pulsed laser, with a sintering temperature of 1200-1300°C and a sintering time of 15-30 minutes; During the sintering process, nano-silicon carbide and silicon nitride self-generate functional ceramic films to enhance material strength and insulation performance; S5. Post-treatment and surface functionalization: After secondary sintering at 800-1000℃, the density and wear resistance are further improved.
5. The method for preparing a bimodal high-strength electrical porcelain according to claim 4, characterized in that: The solid-liquid ratio in the mixed slurry is 50:50, and the dispersant is polyethylene glycol, and the addition amount is 0.5-1%.
6. The method for preparing a bimodal high-strength electrical porcelain according to claim 4, characterized in that: The laser power in the laser self-propagating sintering is 100-500W, and the self-propagating reaction is triggered by 2% metal nitride contained in the powder.
7. The method for preparing a bimodal high-strength electrical porcelain according to claim 4, characterized in that: The holding time of the isostatic pressing is 2-3 minutes.
8. The method for preparing a bimodal high-strength electrical porcelain according to claim 4, characterized in that: The nanobubbles are stabilized by a surfactant, and the bubble injection pressure is 0.1-0.3 MPa.
9. The method for preparing a bimodal high-strength electrical porcelain according to claim 4, characterized in that: The thickness of the functional ceramic film generated during the post-treatment is 0.5-1 μm, which is used to improve the corrosion resistance of the electrical porcelain.
10. The method for preparing a bimodal high-strength electrical porcelain according to claim 4, characterized in that: During the electric field induced alignment process, the applied electric field frequency is 50-100 Hz, which is used to enhance the directionality and density of the particles.